Predictors of Health Seeking Behaviours for Common Childhood Illnesses in Poor Resource Settings in Zambia, A Community Cross Sectional Study - Apuleni, Golden; Jacobs, Choolwe; Musonda, Patrick (Frontiers in Public Health, 2021)
ABSTRACT Background: Developing countries, including Zambia, account for larger share of child morbidities and mortalities due to childhood febrile illnesses. Studies on wider determinants of behaviour pertaining to treatment seeking for childhood febrile illnesses in poor resource settings are limited. This study investigated health seeking behaviours of mothers in poor resource settings of Zambia and identified associated factors. Materials and Methods: Secondary data from a cross sectional study design from the Health for the Poorest Population (HPP) Project was analyzed between March and May 2019. The survey was conducted in 2013 in Samfya and Chiengi in Luapula province and Luwingu and Mungwi in Northern Province of Zambia. A total of 1 653 mothers of children aged less than five years who had diarrhea, malaria, pneumonia or a combination of any of them two weeks prior to the interview were included in the study. Chi square test of independence was carried out to determine the associations between respondent’s demographic characteristics and health seeking behaviour. Multivariable logistic regression was also done to identify predictors of health seeking behaviours for febrile illnesses in under five children in poor resource settings. Result: Among the mothers interviewed, 64.6 % (1 068/1 653) were married while 35.4 % (585/1 653) were unmarried. Their age ranged from 15 years to 58 years. Mothers who sought care for their child for either of the illness accounted for 75.2 % (1 243/1 653) while 24.8 % (410/1 653) did not seek care for their child’s illness. Factors typically associated with health seeking behaviours were mothers’ marital status [aOR=0.74; 95%CI: 0.58-0.94], and mothers ‘level of education [aOR=1.47; 95% CI: 1.13-1.92]. Conclusion: The study found that health seeking behaviours for childhood febrile illnesses in poor resource settings is relatively high and could be predicted by mother’s level of education and marital status. Integrating interventions aimed at improving maternal & child health care with basic education to women and moral support counselling to families may potentially maximise health seeking behaviours in marginalised communities.